Comparison of quality of life evaluated by SF‐36 and DLQI in multibacillary and paucibacillary leprosy patients from Sao Paulo, Brazil. (30th May 2019) - Guimenes Albuquerque, Rachel; Grüdtner Buratto, Gabriel; Hirotsu, Camila; Maeda, Solange M.; Floriano, Marcos C.; Levy Andersen, Monica; Tufik, Sergio; Tomimori, Jane
Abstract: Background: Dermatological diseases have a negative impact on quality of life (QoL), affecting mental and physical health. Leprosy patients usually present with a worse QoL compared with those affected by other conditions. Reactions, neural damage, and pain are some of the consequences that contribute to the lower QoL. However, due to the wide spectrum of the disease, symptoms vary according to leprosy's subtype. This study aimed to compare the QoL between paucibacillary and multibacillary leprosy patients. Individuals were also compared considering the presence of reactions and a correlation between questionnaires was performed. Methods: A total of 104 patients with leprosy aged 18 years old and over were selected. QoL was assessed by the Brazilian‐Portuguese validated versions of the Medical Outcomes Study 36‐item short‐form health survey (SF‐36) and the Dermatology Life Quality Life Index (DLQI). Results: Multibacillary patients showed a more impaired physical function, worse bodily pain, lower score of SF‐36, and higher interference of skin on the performance of daily activities when compared to the paucibacillary group. Individuals without reactions presented lower bodily pain and less effect of the skin on clothing choices compared to those with reactions. The SF‐36 domains exhibited weak correlations with most DLQI questions, and the linear regression model showed that 32% of changes in QoL were related to the skin aspect. Conclusions: Multibacillary leprosy patients have a worse QoL when compared to paucibacillary patients. Reactions played a small role in the QoL of our cohort of patients.